PENGEMBANGAN PERANGKAT PEMBELAJARAN MATERI PROGRAM LINEAR BERBASIS MODEL PROBLEM BASED LEARNING BERBANTUAN GEOGEBRA ANDROID - Sri Ayu Wulaningsih; Sumarni Sumarni; Mohamad Riyadi (Jurnal Edukasi dan Sains Matematika (JES-MAT), 2021)
This study aims to develop mathematics learning tools for linear programming materials based on problem based learning assisted by GeoGebra Android to increase the mathematical problem solving skills of students and to find out the validity of learning tools. Developed learning tools consist of modules, worksheets, and evaluation tools. This development research refers to the Plomp development model consisting of 3 phases, preliminary phase, prototyping phase, and assessment phase. The subjects of the study consisted of 3 validators. The instruments of the study consisted of validation sheets and learning tools in the form of modules, worksheets, and evaluation tools. The data collection technique used was expert validation sheets. The developed learning media were validated by 3 validators consisting of 2 lecturers and 1 teacher. The data analysis technique used was by searching the average of each aspect in the validation sheet so that the average total validator assessment was obtained for each learning tools. Based on the results of learning tools validation, it was obtained the average score of module validation of 4.04 (valid), worksheet validation of 4.18 (valid), and evaluation tool validation of 4.17 (valid). Based on the validator assessment, the results of the study were obtained that developed learning tools are stated valid.